Exploring the communication of oncologists, patients and family members in cancer consultations: development and application of a coding system capturing family‐relevant behaviours (KINcode). Issue 7 (30th October 2015) - Laidsaar‐Powell, Rebekah; Butow, Phyllis; Bu, Stella; Dear, Rachel; Fisher, Alana; Coll, Joseph; Juraskova, Ilona
Abstract: Background: Family members (FMs) regularly attend oncology consultations. However, limited studies have assessed actual behaviours of oncologists, patients and FMs – particularly during decision‐making. The current study aimed the following: (i) to rigorously develop a family (kin) interaction coding system (KINcode) capturing communication and decision‐making behaviours of FMs and family‐relevant behaviours of oncologists and patients and (ii) to apply KINcode to initial oncology consultations. Methods: The 80‐item KINcode system was developed and applied to 72 transcripts of audiotaped medical/radiation oncology consultations including an FM, collected as part of two previous studies. Results: The role of the FM varied considerably within the one encounter, with 33% of FMs assuming three or more roles across the four consultation stages. Whilst most FMs asked treatment decision questions (71%), a minority engaged in other behaviours such as prompting patient questions (4%) or providing information relevant to the decision to the oncologist (18%). Although oncologists rarely initiated interaction with FMs such as in rapport building (18%) or asking FMs questions (25%), they were typically fully responsive to FM questions (90%). Many patients asked their FM a question (42%), but few elicited the FM's decision preferences (4%). Conclusions: This study provides novel insights into the complex nature of family involvement. The findings highlight potentially positive FM‐focused consultation behaviours such as oncologist responsiveness to family questions and potential areas for improvement such as rapport building, invitation of questions and validation of the family's role. Family‐specific communication skills training should be considered in medical student and professional education settings. Copyright © 2015 John Wiley & Sons, Ltd.